Immunizations with diverse sarbecovirus receptor-binding domains elicit SARS-CoV-2 neutralizing antibodies against a conserved site of vulnerability - Burnett, Deborah L.; Jackson, Katherine J.L.; Langley, David B.; Aggrawal, Anupria; Stella, Alberto Ospina; Johansen, Matt D.; Balachandran, Harikrishnan; Lenthall, Helen; Rouet, Romain; Walker, Gregory; Saunders, Bernadette M.; Singh, Mandeep; et al. (Immunity, 2021)
Viral mutations are an emerging concern in reducing SARS-CoV-2 vaccination efficacy. Second-generation vaccines will need to elicit neutralizing antibodies against sites that are evolutionarily conserved across the sarbecovirus subgenus. Here, we immunized mice containing a human antibody repertoire with diverse sarbecovirus receptor-binding domains (RBDs) to identify antibodies targeting conserved sites of vulnerability. Antibodies with broad reactivity against diverse clade B RBDs targeting the conserved class 4 epitope, with recurring IGHV/IGKV pairs, were readily elicited but were non-neutralizing. However, rare class 4 antibodies binding this conserved RBD supersite showed potent neutralization of SARS-CoV-2 and all variants of concern. Structural analysis revealed that the neutralizing ability of cross-reactive antibodies was reserved only for those with an elongated CDRH3 that extends the antiparallel beta-sheet RBD core and orients the antibody light chain to obstruct ACE2-RBD interactions. These results identify a structurally defined pathway for vaccine strategies eliciting escape-resistant SARS-CoV-2 neutralizing antibodies.
CRIS-Team Scopus Importer:2021-11-26
Keywords: antigenic variation; class 4 epitope site; cross-reactivity; epitope conservation; escape mutations; human antibodies; mouse model; neutralization; next generation vaccines; SARS-CoV-2; variants of concern